Synthesis and antiprotozoal activity of mono- and bis-uracil isatin conjugates against the human pathogen Trichomonas vaginalis. Issue 16 (15th August 2015) - Kumar, Kewal; Liu, Nicole; Yang, Donald; Na, Daniel; Thompson, John; Wrischnik, Lisa A.; Land, Kirkwood M.; Kumar, Vipan
Graphical abstract: Synthesis and anti-trichomonas activity of uracil-isatin conjugates. Abstract: A library of mono- and bis-uracil isatin conjugates were synthesized and subjected for the assessment of their in vitro activity against the protozoal pathogen Trichomonas vaginalis . The structure activity studies (SAR) revealed that the bis-uracil-isatin based conjugates were more effective than their corresponding mono conjugates in inhibiting the growth of T. vaginalis at approximately 10 μM with no visual effect on mammalian cells at the same concentration.